2018
DOI: 10.1530/joe-17-0491
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, the placenta and early pregnancy: effects on trophoblast function

Abstract: Pregnancy is associated with significant changes in vitamin D metabolism, notably increased maternal serum levels of active vitamin D, 1,25-dihydroxyvitamin (1,25(OH) 2 D). This appears to be due primarily to increased renal activity of the enzyme 25-hydroxyvitamin D-1α-hydroxylase (CYP27B1) that catalyzes synthesis of 1,25(OH) 2 D, but CYP27B1 expression is also prominent in both the maternal decidua and fetal trophoblast components of the placenta. The precise function of placental synthesis of 1,25(OH) 2 D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 110 publications
1
68
0
2
Order By: Relevance
“…In fact, our previous data suggested that vitamin D therapy for patients with a history of recurrent miscarriage improved immune abnormality with insufficient or deficient vitamin D status, resulting in a prevention of pregnancy loss 6 . In light of this, it has been speculated that vitamin D could act as an immune regulator during implantation and play an important role in reproductive capacity 37,38 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, our previous data suggested that vitamin D therapy for patients with a history of recurrent miscarriage improved immune abnormality with insufficient or deficient vitamin D status, resulting in a prevention of pregnancy loss 6 . In light of this, it has been speculated that vitamin D could act as an immune regulator during implantation and play an important role in reproductive capacity 37,38 …”
Section: Discussionmentioning
confidence: 99%
“…Findings from a recent human study provide evidence that the placenta, working as the interface between mother and fetus, modulates circulating vitamin D metabolites in pregnant women and that it favors the uptake of DBP-bound 25(OH)D3 through a specific receptor system (LRP2-CUBN) (Park et al 2017). In the placenta, CYP27B1 activity is detectable in both maternal decidua and fetal trophoblast, which then allows for local production of 1,25(OH) 2 D from maternal 25(OH)D via 1-alpha-hydroxylase (Ganguly et al 2018). Likewise, both decidua and trophoblast also express VDR (Liu & Hewison 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Placental production of 1,25(OH) 2 D is proposed to be essential for immunosuppressive effects required for immune tolerance of implantation. However, ex vivo and in vitro studies provide evidence for a more extensive role of vitamin D in placental function, including trophoblastic differentiation and extravillous trophoblast invasion of the decidua and myometrium (Ganguly et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D may be beneficial during the establishment of pregnancy, by promoting an immunologically tolerant environment in the decidua and regulating a R73 www.reproduction-online.org Reproduction (2018) 156 R69-R82 number of genes critical for implantation, e.g. CABP9K and HOXA10 (reviewed elsewhere Evans et al 2004, Ganguly et al 2018. Vitamin D also promotes EVT invasion in vitro (Chan et al 2015) and can modulate the inhibitory effects of locally active lipid metabolite sphingosine-1-phosphate (S1P) on EVT migration (Hay et al 2016).…”
Section: In Vitro Studiesmentioning
confidence: 99%